A Tandem Cycling Program: Feasibility and Physical Performance Outcomes in People With Parkinson Disease. Issue 4 (October 2016) - McGough, Ellen L.; Robinson, Cynthia A.; Nelson, Mark D.; Houle, Raymond; Fraser, Gabriell; Handley, Leslie; Jones, Emilie R.; Amtmann, Dagmar; Kelly, Valerie E.
Abstract : Background and Purpose: Individuals with Parkinson disease (PD) have motor and nonmotor impairments that interfere with exercise participation. The purpose of this study was to examine the feasibility and physical performance outcomes of a community-based indoor tandem cycling program that was designed to facilitate a higher cadence, consistency, and intensity of training. Methods: Forty-one participants with mild to moderate PD were enrolled. A high-cadence cycling protocol using mechanically augmented (or forced) exercise on a tandem bicycle was adapted for our program. Participants cycled 3 times per week for 10 weeks. Feasibility measures included program retention, attendance, and adverse events, as well as the ability to reach training goals for heart rate (HR) and cadence. Physical performance outcomes included the Berg Balance Scale (BBS), Short Physical Performance Battery (SPPB), Five-Times-Sit-to-Stand (FTSTS) Test, Timed Up and Go (TUG), and gait parameters during usual and fast-paced walking. Results: Program feasibility was demonstrated with a high attendance rate (96%) and retention rate (100%). There were no adverse events. The majority of participants reached their exercise training goals for target HR (87%) and cadence (95%). Statistically significant physical performance improvement ( P < 0.05) was observed across domains of gait, balance, and mobility, suggesting a slowing or reversal of functional decline as a result of this cycling program. Discussion and Conclusion: Program feasibility and improved physical performance outcomes were demonstrated in individuals with mild to moderate PD participating in a community-based indoor tandem cycling program. Video Abstract available for more insights from the authors (see supplemental digital content 1, http://links.lww.com/JNPT/A146 ). Abstract : Supplemental Digital Content is Available in the Text.